THE EFFECT OF EXTRUSION COOKING ON RESISTANT STARCH FORMATION IN RICE FLOUR SNACK ENRICHED WITH CHICORY ROOT - Đermanović, Branislava; Kojić, Jovana; Krulj, Jelena; Perović, Jelena; Peić Tukuljac, Lidija; Ilić, Nebojša; Bodroža Solarov, Marija (Journal on Processing and Energy in Agriculture, 2021)
The aim of this study was to evaluate the influence of extrusion process variables on the resistant starch content (RS) in a sample of rice snack with added chicory root (addition: from 20-40%). The effect of different levels of feed moisture (16.3 to 22.5%) and a screw speed (500 to 900) rpm, as well as chicory root addition, during extrusion cooking on the resistant starch content of extruded products was investigated. Results of our experiments have demonstrated a decrease in the resistant starch content after extrusion, which is also observed in some other studies. The resistant starch content was in a range of 0.1302 g/100g to 0.5302 g/100g. According to Yoon's model, the screw speed had the greatest negative influence, while the increased feed moisture had a positive effect on resistant starch content, as well as the share of chicory addition.
Keywords: rezistentni skrob, ekstrudiranje, koren cikorije, pirinčano brašno; resistant starch, extrusion, chicory root, rice